INDUSTRIAL LAND: STATE OF THE ART AND MANAGEMENT METHODS. INTERNATIONAL BENCHMARK AND CASE STUDY OF AN INDUSTRIAL ZONE - Nada Laouni; Tarik Ourouadi (African Journal on Land Policy and Geospatial Sciences, 2023)
Context and background The land is a finite resource for which competition is intensifying due to rapid urbanization, population growth, economic necessities... In Morocco, the land is increasingly seen as an obstacle and a major constraint on several levels. . In the industrial sector, the land is an essential lever for investment. In this context, we can cite the issue of the management of industrial zones, which remains a global dilemma. It also raises the issue of the place of the State concerning the private sector in the development, planning, marketing, and management of areas. This study on the issue of industrial land falls within the context of a new ambition that Morocco has set itself, through the Emergence industrial strategy, which aims to accelerate the growth of the industrial sector in certain key sectors of development. This industrial growth should increase the demand for industrial land in the years to come, which makes it all the more urgent to accelerate the reforms underway in this area, and to improve the quality of these industrial zones so that the land issue does not constitute a brake on this expansion. And to properly deal with the problem, we opted for an international benchmark of developing countries that share the same position as Morocco and which manage this type of land in a different way, such as Tunisia and its GMGs, and Turkey with a governing state system and its associations. Goal and Objectives: This document seeks an answer to the question of how to achieve industrial land management that responds to national needs and problems by adopting the experiences of other countries. Methodology: The first part is a bibliographic study and the representation of collected data in the form of graphs. The second part is a documentary analysis which consists of an international benchmark which treats the various modes of management of the industrial zones in Morocco, Tunisia and in Turkey. And finally a qualitative study in the form of a case study, accompanied by a directive interview with representatives of the Ministry of Industry and Market players. Results: it is difficult to speak of an ideal model but the pseudo-perfect model is a model in which the public actors, especially the municipalities, are not fully involved or designated as the main managers of the industrial zones. It is a model where the developer-investor contract takes place under exhaustive specifications and commits the stakeholders. This is the model where urban planning takes the problem of access to land in concrete terms: the status of the bases, the surface and the mobilization.